NEDUTA/NEBOLAI AS A MEDIUM OF ISLAMIC EDUCATION: A QUALITATIVE STUDY OF THE KAILI TRIBE'S PREMARITAL TRADITION - Hairuddin Cikka; M. Iksan Kahar; Mokh. Ulil Hidayat; Nur Eka Wahyuningsih (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Neduta/Nebolai is a premarital proposal ritual among the Kaili people that involves families, customary elders, religious figures, and culturally meaningful symbols. This study examines Neduta/Nebolai as a family- and community-based setting for Islamic education and traces continuity and change in the relationship between local custom and Islam. The study employs a qualitative descriptive design with a historical perspective. Data are drawn from observation, interviews with community informants identified in the field material, documentation, and written sources on Kaili marriage customs. Analysis combines data reduction, thematic categorization, historical interpretation limited to patterns of continuity and change, Islamic educational analysis, and triangulation across sources. The findings identify six major cultural values: respect for women and families, deliberation, polite communication, cultural symbolism, awareness of historical social stratification, and negotiation between custom and religion. Educationally, these values are transmitted through parental and elder modeling, participation by prospective spouses, symbolic communication, family deliberation, and religious practices such as Qur'anic recitation and Barzanji. The study also shows that Islamic compatibility should not be asserted for the tradition as a whole without qualification. The use of kutika to identify auspicious times and explanations of Nokolontigi involving evil spirits, safety, fortune, and longevity require a distinction between cultural function and theological claims. The main contribution of the study is therefore to conceptualize Neduta/Nebolai as a community-based mechanism of Islamic education that links family interaction, customary practice, and premarital learning while subjecting culturally inherited elements to critical Islamic evaluation.